Irrigation areas and irrigation water consumption in the Upper Ili Catchment, NW-China - Thomas Christiansen; Ursula Schöner (Justus-Liebig-Universität Gießen, Zentrum für Internationale Entwicklungs- und Umweltforschung (ZEU), 2004)
This study was mainly based on the interpretation of satellite imagery, supported by only limited field truth data. This approach had to be followed because only very little information on the Upper Ili Catchment was available to the research team. At the same time, however, detailed information on the Upper Ili Basin is essential for the overall framework of this project. The Upper Ili catchment is the main source of the water discharged to the Ili-Balkhash Basin which is mainly located on Kazakhian territory. Hence, the water balance of the Ili-Balkhash Basin crucially depends on the water supply from the Upper Ili region.
Keywords: 330; Bewässerung; China